Revisiting and revamping some novel results in F-metric spaces - Mitrović, Zoran D.; Younis, Mudasir; Rajović, Miloje D. (Vojnotehnički glasnik / Military Technical Courier, 2021)
Introduction/purpose: This article establishes several new contractive conditions in the context of so-called F-metric spaces. The main purpose was to generalize, extend, improve, complement, unify and enrich the already published results in the existing literature. We used only the property (F1) of Wardowski as well as one well–known lemma for the proof that Picard sequence is an F-Cauchy in the framework of F-metric space. Methods: Fixed point metric theory methods were used. Results: New results are enunciated concerning the F-contraction of two mappings S and T in the context of F−complete F-metric spaces. Conclusions: The obtained results represent sharp and significant improvements of some recently published ones. At the end of the paper, an example is given, claiming that the results presented in this paper are proper generalizations of recent developments.